Effects of vitamin D and time delay on bone resorption and bone formation: Mathematical modeling approach - Chontita Rattanakul (2018)
A mathematical model proposed by Rattanamongkonkul et al. [1] is modified here to study the effects of both vitamin D and time delay. Hopf bifurcation theorem is then applied to derive the conditions on the model parameters for which a periodic so lution exists. Computer simulation is also carried out in order to support our theoretical result. Both theoretical and numerical results show that a periodic behavior observed clinically in the level of vitamin D can be expected in our model. Moreover, different kinds of dynamic behavior are investigated numerically.